Fatores de risco e intervenção para controle de sintomas musculoesqueléticos em trabalhadores – estudo de caso e overview de revisões sistemáticas - Faisting, Ana Lucy Rodrigues Ferreira (2019)
Animal care workers are a group of workers that has not yet been studied in relation to the risk factors to which they are exposed in their work environment. Knowledge about these risk factors encouraged a case study and literature search on the effect of ergonomic training to reduce physical demand and musculoskeletal symptoms. Thus, two studies were developed. Study 1 is a case study that aimed to evaluate exposure to risk factors in the work environment of animal handlers. All available workers (n=11) were evaluated through questionnaires and observations of the work process. Study 2 is an overview of systematic reviews that aimed to identify the available evidence on the effectiveness of ergonomic training to reduce physical work demands and musculoskeletal symptoms. We found 42 systematic reviews that evaluated the effectiveness of ergonomic training alone or associated with other types of intervention in different population of workers. The results of Study 1 showed that animal handlers are exposed to several risk factors and have musculoskeletal symptoms. The risk factors identified in this group of workers were: inadequate postures used, manual material handling, excessive physical effort. These risk factors may be responsible for the symptoms in these workers, especially at shoulder, wrist, hand, back, hip, thigh, knee, ankle and feet. The review of systematic reviews conducted in Study 2 did not prove the effectiveness of ergonomic training for the prevention and reduction of musculoskeletal disorders, since the levels of evidence were low and moderate in most of the studies. Then, Study 1 identified the risk factors and musculoskeletal symptoms in animal handlers and Study 2 identified that the ergonomic training does not have sufficient background for its application.